Promoting reading skills in CLIL - Garipova, Nailya; Nicolás Román, Susana (Pulso. Revista de educación, 2016)
Content and Language Integrated Learning (CLIL)has been largely implemented in our educationalinstitutions through different approaches. CLIL canencompass a wide variety of teaching resourcesbut this new framework should constitute an innovative perspective to overcome the restraintsof traditional school curricula in the teaching offoreign languages. Promoting reading skills comprehension is also considered essential in theCLIL approach (Wolff, 2005). However, despite itsimportance, few studies have focused their attention on the reading skills of CLIL in Spain (PérezCañado, 2012). The starting point of this studyremarks the concept of reading as a complex process which involves different skills and strategies,also reinforced by the Common European Framework of Reference for Languages as a key elementin the learning process. The first part of this articlepresents a general framework of CLIL as a methodological approach followed by an overview ofthe reading skill and its main characteristics andpotentiality in the classroom. The second part ofthe article provides guidelines regarding the strategies and types of reading activities that may helpstudents become proficient readers.
Keywords: CLIL; Reading Skills; Proposals